HUBUNGAN ANTARA POLA ASUH ORANGTUA DENGAN PERKEMBANGAN PERSONAL SOSIAL ANAK USIA PRASEKOLAH DI TK THOMAS AQUINO: RELATIONSHIP BETWEEN PARENTING AND PERSONAL DEVELOPMENT OF PRESCHOOLERS (4-6 YEARS) AT THOMAS AQUINO KINDERGARTEN - Sari, Niken Ayu Merna Eka; Alvina, Marcelina Nita; Wati, Ni Made Nopita (Stikes Wira Medika Bali, 2019)
Parenting has a significant impact on the suitability of the child's stage of development in terms of personal-social. Preschool age in terms of personal, children should be able to perform simple activities independently, from the social aspect, the hallmark is the start of the social environment of children. The impact of the failure or delay of personal social development is the frustration of the child because the child is unable to socialize. Selection of appropriate parenting patterns can help the child achieve a normal level of development. The purpose of this study was to determine the relationship between parental parenting with the development of personal social preschoolers. This research uses correlational research design with cross sectional approach. Non probability sampling with purposive sampling technique, the number of samples counted 146 people. The results of the study of 137 respondents apply democratic parenting, 7 respondents implement authoritarian parenting and 2 combinations (democratic-authoritarian). Result of measurement of personal social development, 69 children including normal category and 77 children including category of suspect. The test used is chi square test and Contingency Coefficient test. Chi-square correlation test results obtained p value 0.014, with a significance limit (alpha) of 5%, then p value <0.05. These results indicate that there are differences in personal social development of children in parents who apply democratic, authoritarian or combination parenting. The result of contingency coefficient test, or contingency coefficient is (r) is 0,236, p value 0,014 with very weak correlation conclusion. Nurses are expected to carry out promotive and preventive measures to reduce the rate of personal development of social categories of children suspect, as well as optimizing the child's personal social development.